2006
DOI: 10.1002/jbm.a.30961
|View full text |Cite
|
Sign up to set email alerts
|

Titanate biomaterials with enhanced antiinflammatory properties

Abstract: While titanium implants are generally recognized as having excellent biocompatibility, the mechanistic basis for this has yet to be established. We previously demonstrated that TiO2, found on surfaces of titanium, has antioxidant properties that degrade the reactive oxygen species (ROS) which mediate the inflammatory response. We hypothesized that the antioxidant mechanism was similar to that known to mediate photocatalysis by titanium oxides. Specifically, we investigated whether the electronic or valence sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 88 publications
(150 reference statements)
1
27
0
Order By: Relevance
“…[39][40][41][42] Data presented in this paper suggest better cytokine reduction of TiO 2 coatings on Ti6Al4V and SS, which was consistent to other authors' findings on inflammatory response. There are no reports of comparative analysis between these layers in the literature available.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[39][40][41][42] Data presented in this paper suggest better cytokine reduction of TiO 2 coatings on Ti6Al4V and SS, which was consistent to other authors' findings on inflammatory response. There are no reports of comparative analysis between these layers in the literature available.…”
Section: Discussionsupporting
confidence: 92%
“…According to the study of Contreras et al, titanium oxide reduces the level of reactive oxygen species (free radicals), both neutrophilic and of chemical origin. 42 Another contribution may be the fact that SiO 2 layer has inferior stability than TiO 2 , and it is a partially degradable material, releasing the particles to the environment. 43 The strength of the study is that the analysis was conducted in bone tissue, an environment of the final implant, thus providing information concerned with the target tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of Ti 3+ concentration in the TiO 2 samples, by doping or thermal treatment increases the neutralization activity of the radicals respect to un-changed TiO 2 (33). TiO 2 defects, as Ti 3+ formed from Ti 4+ to compensate oxygen vacancies, play and important role in the neutralization mechanism of radical species.…”
Section: Canillas B Moreno-burriel E Chinarromentioning
confidence: 99%
“…This TiO 2 layer formed blocks the oxidation reaction protecting the metal from an irremediable dissolution (32). Studies have demonstrated that this TiO 2 nanometric film created is responsible of the high biocompatibility of the materials; it is able to neutralize free radicals produced during the inflammatory process associated to the implant procedure (33).…”
Section: Canillas B Moreno-burriel E Chinarromentioning
confidence: 99%
“…However, IL-1a and IL-1ß may be the principal inflammatoninduced cytokines stimulating bone resorption in periodontitis [8][9][10]. In peri-implant crevicular fluid (PICF), higher levels of IL-1ß have been associated with peri-implantitis [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%